2022
DOI: 10.1038/s41598-022-14058-4
|View full text |Cite
|
Sign up to set email alerts
|

Splitting tensile strength and microstructure of xanthan gum-treated loess

Abstract: The tensile strength of loess is closely related to geological disasters. As eco-friendly materials, biopolymers have an excellent strengthening effect on the mechanical properties of soil. The effect of different initial dry densities and xanthan gum (XG) contents on the microstructure and mechanical behavior of XG-treated loess was studied with a series of microscopic tests and splitting tensile tests based on the particle image velocimetry technique. The results show that the XG became concentrated and aggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…So curing period is equally important to get strength in soil. Jiang et al (2022) have performed an STS test on losses soil with XG biopolymer and commented that the formation of fibre interlocking vetoed water loss and increased the STS values. The above studies performed with different types of biopolymers and soil/sand justify that strength enhancement takes place when biopolymer is mixed with any type of soil particles.…”
Section: Resultsmentioning
confidence: 99%
“…So curing period is equally important to get strength in soil. Jiang et al (2022) have performed an STS test on losses soil with XG biopolymer and commented that the formation of fibre interlocking vetoed water loss and increased the STS values. The above studies performed with different types of biopolymers and soil/sand justify that strength enhancement takes place when biopolymer is mixed with any type of soil particles.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, many researchers have begun to study the changes in soil pores from the microscopic perspective. The commonly used methods in geotechnical engineering include mercury injection [32], scanning electron microscopy [33], nuclear magnetic resonance [34], and so on. As shown in Figures 3 and 4, the scanning electron microscope results of the above microscopic tests are more intuitive, and the mercury injection test results can quantify the pore changes in biopolymer-treated soil.…”
Section: Microscopic Mechanism Of Soil Water Retention Improvement By...mentioning
confidence: 99%
“…Regarding splitting and brittle failure, Jiang et al [32] concluded that different initial dry densities and xanthan gum contents had different effects on the mechanical properties of loess treated with xanthan gum. With the increase in the xanthan gum content, the strain softening phenomenon was more obvious, and the splitting tensile strength and brittleness of the sample increased.…”
Section: Effects Of Types and Ratios Of Biopolymers On The Mechanical...mentioning
confidence: 99%
“…In one laboratory experiment, the addition of 0.2% guar gum increased the unconfined compressive strength of loess soil by up to 50% compared to untreated soil [5]. Another study found that the addition of 0.2% xanthan gum increased the elastic modulus and shear strength of loess soil by up to 180% and 77%, respectively [4]. Note that the exact improvement in soil properties depends on many factors, namely soil type, biopolymer type and concentration, and curing time, and may vary for different soils and biopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies investigated the effects of biopolymers on the geotechnical properties of loess soil. Tong et al [4] found that guar gum injection can significantly increase the unconfined compressive strength of loess soil, while also reducing soil permeability. Also, xanthan gum can improve the elastic modulus and shear strength of loess soil and its effectiveness is related to the concentration used.…”
Section: Introductionmentioning
confidence: 99%